2022
DOI: 10.1111/jfpp.16489
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of poly(butylene adipate‐ co ‐terephthalate) ( PBAT ) antimicrobial films with clove and cinnamon essential oils

Abstract: Packaging is a physical barrier that separates the product from the outside. It is also possible to add active agents to the packaging so that it becomes active, extending the shelf life of products. Antimicrobial active packaging uses antimicrobial agents, such as essential oils, to inhibit or delay microbial growth in food. The objective of this work is to produce active packaging made of poly(butylene adipate‐co‐terephthalate), a biodegradable polymer, that uses essential oil as an antimicrobial agent. To a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Moreover, the recent studies [21][22][23] have witnessed rapid development of the use of CIEO as an adjunctive therapy in enhancing symptoms of depressive and anxiety disorders. It was found that CIEO essential oil composed of more than 20 constituents; however, the major constituent in the CIEO was cinnamaldehyde, which identified by GC-MS to be ~ 81% of the oil [24], in addition to benzaldehyde (~ 6.70%), cinnamyl ester (~ 6.10%), coumarin (~ 3.20%), camphene (~ 1.70%), and other components. These constituents possess phenolic structure and aldehyde and ketone groups that are notably having positive antimicrobial and antiviral effects [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the recent studies [21][22][23] have witnessed rapid development of the use of CIEO as an adjunctive therapy in enhancing symptoms of depressive and anxiety disorders. It was found that CIEO essential oil composed of more than 20 constituents; however, the major constituent in the CIEO was cinnamaldehyde, which identified by GC-MS to be ~ 81% of the oil [24], in addition to benzaldehyde (~ 6.70%), cinnamyl ester (~ 6.10%), coumarin (~ 3.20%), camphene (~ 1.70%), and other components. These constituents possess phenolic structure and aldehyde and ketone groups that are notably having positive antimicrobial and antiviral effects [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that CIEO essential oil composed of more than 20 constituents; however, the major constituent in the CIEO was cinnamaldehyde, which identified by GC-MS to be ~ 81% of the oil [24], in addition to benzaldehyde (~ 6.70%), cinnamyl ester (~ 6.10%), coumarin (~ 3.20%), camphene (~ 1.70%), and other components. These constituents possess phenolic structure and aldehyde and ketone groups that are notably having positive antimicrobial and antiviral effects [24][25][26]. On the other hand, they can be promoted the noncovalent interactions via the hydrogen bonding linkages.…”
Section: Introductionmentioning
confidence: 99%
“…These halos' diameters can be classified as sensible because they are greater than 20 mm [24] . In the literature, there isn't any report about PBAT antimicrobial activity, and a study conducted by Moraes et al [6] confirmed this property because their neat PBAT films were submitted to an antimicrobial test, and bacteria grew normally without any resistance. Antimicrobial activity was higher in Gram-positive bacteria than Gram-negative bacteria, as observed in this study, due to their structure [25] .…”
Section: Antimicrobial Activity Analyses Of Oilmentioning
confidence: 99%
“…It's a very interesting material for the packaging sector. Petrochemical in origin, the PBAT has mechanical qualities like low-density polyethylene, including high elongation at break and toughness [6] . Its compatibility, fabricability, and flexibility make it a promising material for a variety of applications, including packaging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation